Representasi Satire pada Lirik Lagu “Gugatan Rakyat Semesta” Karya .Feast - Afrida, Dewi; Triana, Yelmi; Kusumanegara, Afdhal; Marlisa, Welli; Sardila, Vera (Gurindam: Jurnal Bahasa dan Sastra, 2025)
This study examines the satirical language style in the lyrics of the song “Gugatan Rakyat Semesta” by the band .Feast using a cognitive semantic approach. This approach is used to reveal the hidden meaning behind the use of words and phrases in the song lyrics as a form of social criticism. The method used is the distribution method which begins with the application of the basic technique of Direct Element Sharing and is continued with advanced techniques in the form of expansion techniques. The results of this study indicate that there are seven words and eight phrases that contain satirical elements. Cognitive semantics is used to help reveal the critical and stylistic cognition of the music group .Feast. The lyrics of the songs studied reflect the cognition of the music group .Feast which is critical and has its own style. The satirical language style used functions as a means of social criticism that is packaged aesthetically and communicatively in musical works.